Nem kognitív készségek kereslete és kínálata a munkaerőpiacon - Fazekas Károly (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
– Non-cognitive skills are important predictors of success on the labour market and in many areas of economic and social life. This paper explores the current literature on the economics of non-cognitive skill formation and the most important explanatory factors behind the recent boost of the predictive power of non-cognitive skills over life cycles. It shows how the ongoing information revolution changes the task content of professions and how this change can re-evaluate the returns of cognitive and non-cognitive skills on the labour market. The most effective tools of noncognitive skill development in different life periods are discussed and the results of the impact evaluation of different measures are summarized.
Keywords: I21; I26; I28; J24; Z13; 330; non-cognitive skills; technological revolution; human capital investment; education policy